Nuclear Glycogen Inclusions in Canine Parietal Cells. (May 2017) - Silvestri, S.; Lepri, E.; Dall'Aglio, C.; Marchesi, M. C.; Vitellozzi, G.
Nuclear glycogen inclusions occur infrequently in pathologic conditions but also in normal human and animal tissues. Their function or significance is unclear. To the best of the authors' knowledge, no reports of nuclear glycogen inclusions in canine parietal cells exist. After initial observations of nuclear inclusions/pseudoinclusions during routine histopathology, the authors retrospectively examined samples of gastric mucosa from dogs presenting with gastrointestinal signs for the presence of intranuclear inclusions/pseudoinclusions and determined their composition using histologic and electron-microscopic methods. In 24 of 108 cases (22%), the authors observed various numbers of intranuclear inclusions/pseudoinclusions within scattered parietal cells. Nuclei were characterized by marked karyomegaly and chromatin margination around a central optically empty or slightly eosinophilic area. The intranuclear inclusions/pseudoinclusions stained positive with periodic acid–Schiff (PAS) and were diastase sensitive, consistent with glycogen. Several PAS-positive/diastase-sensitive sections were further examined by transmission electron microscopy, also using periodic acid-thiocarbohydrazide-silver proteinate (PA-TCH-SP) staining to identify polysaccharides. Ultrastructurally, the nuclear inclusions were composed of electron-dense particles that were not membrane bound, without evidence of nuclear membrane invaginations or cytoplasmic organelles in the nuclei, and positive staining with PA-TCH-SP, confirming a glycogen composition. No cytoplasmic glycogen deposits were observed, suggesting that the intranuclear glycogen inclusions were probably synthesized in loco . Nuclear glycogen inclusions were not associated with gastritis or colonization by Helicobacter-like organisms ( P > .05). Our findings suggest that nuclear glycogen inclusions in canine parietal cells could be an incidental finding. Nevertheless, since nuclear glycogen is present in several pathologic conditions, further investigations could be warranted to determine their true significance.